Protease-activated receptor 1 is the primary mediator of thrombin-stimulated platelet procoagulant activity - Andersen, Henrik (The National Academy of Sciences, 1999)
The activation of human platelets by thrombin is mediated primarily by protease-activated receptors (PARs). PAR1 and PAR4 are present on human platelets and are activated by the hexapeptides SFLLRN and GYPGQV, respectively. To further characterize the involvement of PAR1 and PAR4 in platelet activation, the ability of SFLLRN or GYPGQV to generate annexin V binding to newly exposed phospholipids on the platelet surface and generate procoagulant activity has been examined. Exposure of phosphatidylserine and phosphatidylethanolamine on platelets, as determined by an increase in annexin V binding, was strongly stimulated by SFLLRN, thrombin, and collagen, but only to a minor extent by GYPGQV. In a clotting assay initiated with factor VIIa, soluble tissue factor, and calcium, the clotting time in the absence of platelets was >5 min. In the presence of unstimulated platelets, the clotting time was 200 ± 20 sec. In the presence of platelets activated with SFLLRN or collagen, the clotting time decreased to 100 ± 10 sec. This shortening of the clotting time is equivalent to about a 5-fold increase in coagulant activity when stimulated platelets are compared with unstimulated platelets and activated platelets are used as a reference. These results indicate that thrombin initiates a very strong response in platelets through PAR1, leading to exposure of anionic phospholipids that support blood clotting. The response mediated by PAR4, however, was limited to platelet aggregation and similar to that triggered in platelets by weaker agonists such as ADP or epinephrine.